De rutilo metri Graeci nomine - Novikova, Ekaterina (Hyperboreus, 2019)
The paper deals with the interpretation of the gloss rutilum (an alternative name for a trochee), which was attributed to the language of the Aurunci by Diomedes. The Auruncan language, according to the standard view, is a North-Oscan dialect  that used a version of the Etruscan alphabet. In this alphabet, Y with a point at the top corresponds to the letter O, while a simple Y corresponds to the letter V. The gloss could be thus read as *rotilom. The next problem is the suﬃx -il-, which E. Forcellini treated as equivalent to the diminutive suﬃx -ul- (rotulus). This paper argues that what lies behind -il- is instead Oscan -ii-.